2003
DOI: 10.1590/s0037-86822003000300013
|View full text |Cite
|
Sign up to set email alerts
|

Miocardiopatia dilatada em pacientes com infecção chagásica crônica: relato de dois casos fatais autóctones do Rio Negro, Estado do Amazonas

Abstract: Dois casos fatais de miocardiopatia chagásica crônica dilatada são relatados pela primeira vez em pacientes autóctones do rio Negro, Estado do Amazonas. Ambos os casos, um homem de 45 anos de idade e uma mulher de 44, nasceram e viveram toda a vida na região do Rio Negro, no norte do estado do Amazonas, tendo sido picados numerosas vezes por triatomineos silvestres em piaçabais da área. Os pacientes que tiveram as reações sorológicas positivas para anticorpos anti-Trypanosoma cruzi (imunofluorescência, ELISA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 12 publications
(7 reference statements)
2
29
1
5
Order By: Relevance
“…No reagent serum (neither inconclusive reactions) was found in children and youths, which suggests that the vector transmission is not occurring in the region. Contrasting this data, in the City of Barcelos, State of Amazonas, eighteen children under 10 years of age were found positive for T. cruzi 23 . Two autochthonous cases were found in Rio Negro, Amazon, and both died from chronic Chagas myocardiopathy 24 .…”
Section: Discussioncontrasting
confidence: 80%
“…No reagent serum (neither inconclusive reactions) was found in children and youths, which suggests that the vector transmission is not occurring in the region. Contrasting this data, in the City of Barcelos, State of Amazonas, eighteen children under 10 years of age were found positive for T. cruzi 23 . Two autochthonous cases were found in Rio Negro, Amazon, and both died from chronic Chagas myocardiopathy 24 .…”
Section: Discussioncontrasting
confidence: 80%
“…Serological surveys and cross-sectional studies carried out by Fundação Nacional de Saúde from 1975-1980, in different states in the Brazilian Amazon Region, and by Coura et al from 1971Coura et al from -2002 in AM showed prevalences ranging from 2.4-13.2% (Camargo et al 1984, Coura et al 1999. Severe chronic cases of Chagas disease have also been reported in the Brazilian Amazon Region (Albajar et al 2003, Junqueira et al 2005, Xavier et al 2006). …”
Section: Chagas Disease In the Amazon Regionmentioning
confidence: 96%
“…Taking into considering the small number of patients, it was not possible to safely evaluate the real morbidity of Chagas disease. However, typical and fatal cases of chronic Chagas heart disease have been described in this area 94,95 .…”
Section: Areas Of Low Morbiditymentioning
confidence: 99%
“…Over the last 20 years (1991-2011), we have developed seroepidemiological surveys and clinical, radiological and electrocardiographic studies among populations that were seropositive for Chagas infection, in the middle and upper regions of the Negro River, in the State of Amazonas [72][73][74][76][77][78] . Several typical and fatal chronic cases of Chagas disease were described 94,95 , involving more than 7,000 screening serological reactions and more than 300 confirmatory serological reactions. In three preliminary seroepidemiological surveys conducted in 1991, 1993 and 1997, we carried out 2,254 screening serological reactions using IIF on blood collected on filter paper and found that the mean positivity rate was 13% 76 , although only 2.5% to 5% were confirmed by means of serum IIF, ELISA and trypomastigote excreted-secreted antigens (TESA)-blot.…”
Section: Morbidity Of Chagas Disease In the Amazon Regionmentioning
confidence: 99%